Identification, expression patterns and RNA interference of Capa peptide receptors in Dendroctonus armandi larvae under cold. (19th October 2021) - Fu, Danyang; Sun, Yaya; Liu, Bin; Ning, Hang; Wang, Linjun; Chen, Hui
Abstract: Capa peptides are of great importance for both understanding the control of salt balance by neuropeptides and revealing the mechanisms of response to cold stress. Presently, research on the physiological function of neuropeptides typically includes identifying and analysing specific receptors and their interactions. Given their role in osmotic balance and the importance of cold tolerance, this study attempted to identify the sequence and function of Capa peptide receptors (CapaRs) in Dendroctonus armandi and to prove that CapaRs play an important role in the cold stress responses. In this study, two full‐length cDNAs encoding more than 400 amino acids of Dendroctonus armandi Capa peptide receptor genes (DaCapaRs) and their sequence features were identified using bioinformatic analysis methods. The alignment of DaCapaRs with homologous proteins from other species indicated that the most similar are Dendroctonus ponderosae Capa peptide receptors. The expression of DaCapaRs was high in December and in the larvae, adults and head and midgut of Dendroctonus armandi . In addition, with decreasing temperatures and long‐term exposure to cold conditions, the expression of DaCapaRs increased markedly when the temperature was 4 to –10°C. RNA interference analysis demonstrated that DaCapaRs play an important role in the cold tolerance of overwintering larvae and indicated that a reverse interaction occurs between DaCapaRs and aquaporins. The results showed that DaCapaRs play an essential role in understanding the neuropeptide regulation of cold tolerance in overwintering Dendroctonus armandi larvae and that it can assist in understanding adaptive evolution of Dendroctonus armandi and its relationship with the ecological environment of the Qinling Mountains.